History in Motion: Nūr al-Dīn al-Rānīrī’s Retelling of ʿAbbāsid History in Seventeenth Century Aceh - Meyer, Verena (Fakultas Agama Islam, Universitas Muhammadiyah Yogyakarta, 2024)
This article focuses on the seventeenth-century Islamic scholar Nūr al-Dīn al-Rānīrī (d. 1658), who became especially known for his harsh oppression of monistic Sufism during his tenure as Shaykh al-Islām at the Acehnese court. Yet, some indications suggest that Rānīrī’s opposition to Sufism was not as clear-cut as it first seems. Revisiting a thus-far unanswered question about a strange idiosyncrasy in Rānīrī’s magnum opus, a universal history in Malay titled Bustān al-Salāṭīn, this article seeks to dislodge simplistic understandings of the legitimacy of certain strands of Sufism, the polemics around charges of being “monistic,” and Rānīrī’s own positionality.